Presence and extent of histological tumour necrosis is an adverse prognostic factor in papillary type 1 but not in papillary type 2 renal cell carcinoma. Issue 2 (7th September 2012) - Pichler, Martin; Hutterer, Georg C; Chromecki, Thomas F; Pummer, Karl; Mannweiler, Sebastian; Zigeuner, Richard
Abstract : Aims: To date, only limited information is available on the prognostic significance of the presence and extent of histological tumour necrosis with regard to papillary renal cell carcinoma (RCC) types 1 and 2 subclassification. Thus, the aim of this study was to evaluate the prognostic impact of these pathological features on the clinical outcome in papillary subtypes. Methods and results: The influence of histological tumour necrosis on the clinical outcome in 177 patients with papillary RCC was evaluated. For papillary subtype 1, the presence of histological tumour necrosis was an independent negative prognostic factor for disease‐free survival ( P = 0.039), and a greater extent of necrosis (>20%) was significantly associated with both poor disease‐free and overall survival ( P = 0.033 and P = 0.041, respectively). Regarding papillary subtype 2, neither the presence nor extent of histological tumour necrosis was a statistically significant negative prognostic factor. Conclusion: Our findings suggest that the presence and extent of histological tumour necrosis are independent prognosticators in papillary RCC subtype 1, but not in papillary subtype 2. Thus, previously reported conflicting data regarding the prognostic impact of tumour necrosis in papillary RCC might be explained, in part, by heterogeneous subtypes.